2011
DOI: 10.1371/journal.pone.0017468
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Diagnostic Model for Predicting Influenza among Young Adult Military Personnel with Febrile Respiratory Illness in Singapore

Abstract: IntroductionInfluenza infections present with wide-ranging clinical features. We aim to compare the differences in presentation between influenza and non-influenza cases among those with febrile respiratory illness (FRI) to determine predictors of influenza infection.MethodsPersonnel with FRI (defined as fever≥37.5°C, with cough or sore throat) were recruited from the sentinel surveillance system in the Singapore military. Nasal washes were collected, and tested using the Resplex II and additional PCR assays f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
(15 reference statements)
3
21
1
Order By: Relevance
“…It has been reported in other populations that multiple respiratory viruses such as parainfluenza virus, rhinovirus, adenovirus, metapneumovirus, respiratory syncytial virus (RSV), and coronavirus can cause ILI, 4 but the virologic etiology varies greatly among geographic locales, age groups, seasons, and years. [5][6][7][8][9][10][11][12][13] Some studies have suggested that specific symptoms could be used for the clinical prediction of the etiology of ILI, [14][15][16][17][18] though most of these studies only compared influenza to noninfluenza etiology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in other populations that multiple respiratory viruses such as parainfluenza virus, rhinovirus, adenovirus, metapneumovirus, respiratory syncytial virus (RSV), and coronavirus can cause ILI, 4 but the virologic etiology varies greatly among geographic locales, age groups, seasons, and years. [5][6][7][8][9][10][11][12][13] Some studies have suggested that specific symptoms could be used for the clinical prediction of the etiology of ILI, [14][15][16][17][18] though most of these studies only compared influenza to noninfluenza etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating infections caused by influenza viruses from those caused by other respiratory viruses is essential for case management, as illustrated during the 2009 A/H1N1 influenza pandemic (A/H1N1p). Many definitions of influenza-like illness (ILI) have been used worldwide in influenza surveillance; however, the sensitivity and positive predictive value of such definitions significantly vary depending on the co-circulation of other respiratory viruses in the community [Boivin et al, 2000;Lee et al, 2011;Thursky et al, 2003]. The identification of the respiratory viruses that are responsible for influenza-like illness has been reported in many countries, and the percentage of positive swabs for at least one virus ranges from 32% to 65% [Bellei et al, 2008;Laguna-Torres et al, 2009;Ren et al, 2009;Buecher et al, 2010;Renois et al, 2010;Razanajatovo et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…18 Symptoms including nausea/vomiting, myalgias, and headache have all been previously reported more commonly in patients with influenza than in influenza-negative patients. 10,19,20 In our study, children with influenza were older (median age 9.4 years) than children who tested negative for influenza (median age 5.5 years), which may indicate varying patterns of exposure and immunity within age groups. The other etiologies of ILI in this community need to be further explored.…”
Section: Discussionmentioning
confidence: 62%
“…Predictive models for influenza were constructed separately for children and adults using multivariable logistic regression and generally following previously described methods. 10 In our analyses, any sociodemographic feature or clinical variable that had a P value less than 0.05 on bivariable analysis was included in the predictive model, with the exception of variables related to 1) finances and productivity, 2) the anatomic location of sampling, and 3) diagnoses and treatment received. These variables were not included as they were considered either minimally relevant to a clinical predictive model or unavailable at the time a clinician would be using the model.…”
Section: Methodsmentioning
confidence: 99%